Software-based Attention Bias Modification Intervention for Adult EFL Learners’ Foreign Language Anxiety - Hashemi, Mohammad R.; Alizadeh Oghyanous, Parastoo; Bakhtiarvand, Morteza (Journal of Educational Technology and Instruction, 2024)
Foreign language anxiety has long been considered detrimental to second language acquisition to the extent that some teaching methods were based on anxiety reduction in language classrooms. Cognitive bias modification is an almost new procedure for reducing anxiety and depression. The current mixed methods study aimed at investigating the effect of software-based attentional CBM on adult Iranian EFL learners’ language anxiety. Participants of the study were 79 English language learners (M = 23.73, SD = 1.42), selected based on convenience sampling from three foreign language institutes in Tehran. The distribution of gender was almost equal. Data were collected through Foreign Language Classroom Anxiety Scale before and after applying the software-based attentional bias modification intervention. Furthermore, semi-structured interviews were run to explore how this treatment would affect the anxiety level of language learners. Analysis of Covariance results revealed that the software-based attentional bias modification significantly reduced foreign language anxiety of the learners. Furthermore, analysis of the qualitative data showed that attentional bias modification mainly affects the communication apprehension and test anxiety components of foreign language anxiety.